2017
DOI: 10.1007/s00234-017-1860-9
|View full text |Cite
|
Sign up to set email alerts
|

Subject-specific regional measures of water diffusion are associated with impairment in chronic spinal cord injury

Abstract: DTI tractography-driven, subject-specific injury demarcation approach provided measures that were more specific to impairment. Notably, DTI indices obtained from the IRRI region showed the highest specificity to impairment, demonstrating their strong potential as biomarkers for the SCI severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Several human and animal studies have shown the relative importance of the cord above and below the level of injury in SCI patients. [35][36][37] With that goal, we decided to investigate the differences between DTI and DTT measures of the following groups: 1) between normal and SCI group; 2) in cervical SCI, only the thoracic slices (which is the common region for all cervical SCI no matter where the level of injury is) was compared with the thoracic average of the normal population; and 3) in the thoracic SCI group, the cervical area (which is the common region for all thoracic SCI no matter where the level of injury is) was compared with the cervical average of the normal group. Although our group results showed that in the cord above (in thoracic injury patients) and below (in cervical injury patients) there were statistically significant changes compared to the normal healthy controls, our sample size was small to deduce the utility of these findings to a single subject's treatment and rehabilitation status.…”
Section: Figmentioning
confidence: 99%
“…Several human and animal studies have shown the relative importance of the cord above and below the level of injury in SCI patients. [35][36][37] With that goal, we decided to investigate the differences between DTI and DTT measures of the following groups: 1) between normal and SCI group; 2) in cervical SCI, only the thoracic slices (which is the common region for all cervical SCI no matter where the level of injury is) was compared with the thoracic average of the normal population; and 3) in the thoracic SCI group, the cervical area (which is the common region for all thoracic SCI no matter where the level of injury is) was compared with the cervical average of the normal group. Although our group results showed that in the cord above (in thoracic injury patients) and below (in cervical injury patients) there were statistically significant changes compared to the normal healthy controls, our sample size was small to deduce the utility of these findings to a single subject's treatment and rehabilitation status.…”
Section: Figmentioning
confidence: 99%
“…DWI stitching is difficult to perform and is sensitive to artifacts produced by respiratory and cardiac movements at the thoracic level of the spinal cord 9,57 . Nonetheless, several teams 14,58,59 have aimed to perform DWI and tractography of the entire spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…1 Performing spinal cord tractography, which requires extreme precision, is the last step of the DWI processing chain; it results in a long pipeline of data acquisition, processing, and modeling. 2 As several studies have reported, spinal cord tractography is of diagnostic interest for a wide range of pathologies (intramedullary tumor, 3,4 vascular malformations, 5,6 dysraphism, 7 spinal cord injury, 8,9 multiple sclerosis 10,11 ). To date, spinal cord tractography is not used in routine clinical practice because of difficulties in producing a rendering consistent with the anatomical truth.…”
Section: Introductionmentioning
confidence: 99%
“… 153 , 154 Diffusion tensor imaging quantifies axonal pathway disruption, while magnetization transfer imaging signal changes have been associated with neurological function and outcomes. 155 , 156 Currently, MRI is primarily used as a structural as opposed to mechanistic molecular biomarker but functional MRI, connectomics, spectroscopy, and integration with neurophysiology may reveal mechanistic changes related to the evolution of post-SCI phenotypic states such as neuropathic pain. 157 Projects such as Enhancing Neuroimaging Genetics through Meta-Analysis (ENIGMA) correlate brain structure changes to regional gene expression.…”
Section: Biomarker Modeling In Sci Prediction and Prognosticationmentioning
confidence: 99%